Rhizaxinella nuda Wilson 1925 ... - Plotkin, Alexander S.; Janussen, Dorte (Zenodo, 2008)
Rhizaxinella cf. nuda Wilson, 1925 (Fig. 15) Synonymy Rhizaxinella nuda— Wilson 1925: 352 –353, pl. 38 (fig. 5). Description External morphology. Small clubshaped sponges with rather damaged stalks (figs. 15A–E). Their height varies from 0.6 to 2.1 cm. The surface is velvety, greyish. Consistency is rather soft. A contracted osculum is located slightly eccentrically on the top of main body. Skeleton. The choanosomal skeleton is constituted by the principal tylostyles arranged more or less radially and grouped in tracts or bundles (fig. 15F). The ectosomal skeleton is formed by the bouquets of small tylostyles, densely packed and intermingled. Skeleton of the stalk not observed because of considerable damage of the latter. Spicules. Altogether 120 spicules from 2 specimens were measured. Two size categories are well distinguished. The number of measured spicules of each category is given below, separately for each specimen (n1, n2). Both principal and ectosomal spicules possess welldeveloped spherical ... : Published as part of Plotkin, Alexander S. & Janussen, Dorte, 2008, Polymastiidae and Suberitidae (Porifera: Demospongiae: Hadromerida) of the deep Weddell Sea, Antarctic *, pp. 95-135 in Zootaxa 1866 on pages 126-128, DOI: 10.5281/zenodo.183878 ...